Validity Test of Android-Based Learning Media Assisted by Ispring Suite on Pythagorean Theorem Material - Triayuningsih Permata Suci; Sunismi Sunismi (IKIP Mataram, 2024)
The development of technology today has a great influence on human life. This influence also includes the use of technology in education, such as the utilization of learning media connected to information technology. This research was conducted to validate the use of learning media in the form of Android applications with the help of iSpring Suite in learning Pythagorean Theorem material. The research method used is RnD by applying the ADDIE model. The research subjects consisted of 3 experts, one practitioner, and 5 grade VIII students. Data collection involved qualitative and quantitative data. The results of the analysis showed that the experts gave an average assessment of 92.09% with the category